Implementasi Pemilihan Pasangan Hidup yang Ideal Dalam Membentuk Keluarga Harmonis Perspektif Maqashidu Syariah - Febiana, Fenni; Hayati, Yassir (Published by Institut Teknologi Pendidikan Indonesia, 2023)
Islam has regulated all aspects of human life starting from the time a person is born until the person dies. Likewise, with the problem of choosing a partner in order to form a harmonious family, great attention must be paid to choosing a partner. This research uses qualitative methods with the type of library research, collecting data by searching for sources and reconstructing them from various sources such as books, both primary and secondary books that discuss partner selection in Islam, and also journals. There are 3 scientific works in the form of journals used in this research, namely the first, a journal by Avan Antoni, Moh Salih, Najiburrahman, The second, a Journal by Aini Mahmud entitled, The third is Nurul Najwah's. The results of the research are that there are five Maqashid Syariah Al-Kulliyat Al-Khams (five core or main things), namely: Maintaining religion (hifz ad-din), protecting the soul (hifz an-nafs), maintaining reason (hifz al-aql) , Protecting wealth (hifz al-mal), Protecting descendants (hifz an-nash). In this case, it can be understood that the implementation of selecting an ideal life partner in Maqasidus Syariah is Maintaining Religion (hifz ad-din) and Protecting Offspring (hifz an-nash). By choosing an ideal life partner according to Islamic law, you will strengthen the religious foundation in the household, and also get good offspring, namely pious and pious children.